Centre of pressure golf swing movement strategies are better defined using a continuous approach than by segregated styles - Jones, K. M.; Wallace, E. S.; Otto, S. R. (Journal of Sports Sciences, 2023)
The relationships between movement style and golf performance have been well researched, but the premise of segregated movement styles has not been fully examined. The purpose of this investigation was to examine the postulation that centre of pressure data are not best described by segregated styles but instead by a continuum and to determine relationships between centre of pressure, handicap and clubhead speed using a continuous approach. Centre of pressure paths of driver and 5-iron shots from 104 amateur golfers were analysed using discrete and continuous methods. Discrete methods used different cluster evaluation criteria which result in two-cluster and twenty-cluster solutions being considered "optimum". The two-cluster solution showed the characteristics of "front-foot" and "reverse" centre of pressure styles. However, a continuous principal component analysis method revealed that the clusters were not well separated and provided support for a multidimensional continuum. The principal components had a high correlation with handicap and clubhead speed. Lower handicap and higher swing speed golfers tended to display a centre of pressure with a "front-foot" style and a fast transition towards the front foot at the start of the downswing. A continuous characterisation of centre of pressure styles has more utility than the segregated styles previously described.